Gradient plate ceramic-based mixed matrix membrane material as well as preparation method and application thereof

By spin-coating and cross-linking an amino-modified UiO-66 and PVA solution onto an alumina gradient flat ceramic substrate, a mixed matrix membrane with a gradient pore structure is formed. This solves the interfacial compatibility and mass transfer resistance problems of mixed matrix membrane materials, achieving high-efficiency separation performance and mechanical stability, and is suitable for the treatment of wastewater from new energy vehicle coating and textile printing and dyeing.

CN121016522APending Publication Date: 2025-11-28HEFEI UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511379529.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-25
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing hybrid matrix membrane materials suffer from insufficient compatibility at the filler-polymer interface, high substrate mass transfer resistance, and weak interfacial bonding, resulting in inadequate separation and stability of the composite membrane. Furthermore, the preparation process is complex, costly, and environmentally unfriendly.

Method used

A method combining gradient plate ceramic substrates with amination-modified UiO-66 nanoparticles was adopted. Amination-modified UiO-66 and PVA solution were spin-coated onto an alumina gradient plate ceramic substrate, and cross-linked with glutaraldehyde to form a mixed matrix film with a gradient pore structure, which enhances filler dispersibility and interfacial bonding strength.

Benefits of technology

It improves the filtration flux and ion rejection rate of composite membranes, enhances mechanical stability, reduces preparation costs and energy consumption, adapts to complex environments, and has the potential for industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121016522A_ABST
    Figure CN121016522A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic separation membrane preparation, in particular to a gradient plate ceramic-based mixed matrix membrane material as well as a preparation method and application thereof. The specific preparation technology comprises the following steps: dipping a substrate in a glutaraldehyde solution for a set time, and drying for later use; the preparation method comprises the following steps: activating UiO-66 in methanol, dispersing the activated UiO-66 in deionized water, adding an amino source component for reaction, centrifugally collecting aminated UiO-66, adding the aminated UiO-66 into a polyvinyl alcohol solution, and stirring to obtain mixed matrix membrane slurry; and spin-coating the slurry on a pretreated substrate, drying, immersing into a glutaraldehyde solution for cross-linking reaction, and drying to obtain the gradient flat plate ceramic-based mixed matrix membrane. By optimizing the multi-scale structures of the substrate and the separation layer membrane material, the problems of poor dispersity, weak interface bonding and high substrate mass transfer resistance of the separation layer filler are solved, and the membrane material and the preparation method provided by the invention have the advantages of selectivity, mechanical stability and green process.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of ceramic separation membrane preparation, and particularly relates to a gradient flat plate ceramic-based mixed matrix membrane material and a preparation method and application thereof. BACKGROUND

[0002] With the increasingly serious problem of water pollution, it is urgent to develop efficient water treatment technology. Membrane separation technology is widely used due to its low cost, small land occupation and other advantages.

[0003] Mixed matrix membranes (MMMs) can combine the processability of organic polymers and the selective separation advantage of inorganic materials by dispersing inorganic nanofillers in the polymer matrix, and have broad application prospects in wastewater treatment, heavy metal ion interception and pervaporation. However, there are still significant technical bottlenecks in material design and structure regulation of MMMs, which restrict the separation and permeability of composite membranes (Zhang H, Wu Y H. Preparation, modification of MOF-polymer mixed matrix membranes and their application in pervaporation [J]. Chemical Progress, 2023, 35(08): 1154-1167.).

[0004] Firstly, the lack of compatibility of the filler-matrix interface is a key factor limiting the performance of MMMs. Poor compatibility of the filler-polymer interface mainly manifests in the following aspects: differences in surface chemical properties leading to filler agglomeration, uneven dispersion of physical blending, weak interfacial bonding force causing defects, and excessive modification blocking the filler channels or sacrificing mechanical properties, which restricts the selective separation efficiency and long-term stability of the composite membrane. Patent CN115228311A discloses a preparation method of PIM-1 mixed matrix membrane based on amine oxime group modified UiO-66 material, which constructs a hydrogen bond network by introducing amine oxime groups to functionalize the filler directionally. However, this method has the problems of complex process and limited precision matching of specific filler-matrix interface bonding, which is difficult to universally solve the interface defect problem.

[0005] Secondly, the problems of insufficient substrate mass transfer resistance and interface bonding force have not been effectively solved for a long time. Traditional ceramic substrates mostly adopt single-hole structure design, resulting in high fluid mass transfer resistance, and the low surface roughness of the substrate leads to the formation of pinhole defects when the polymer separation layer is covered, and the interface peeling is easily caused by stress concentration under high pressure operation. Patent CN112023732A discloses a forward osmosis composite membrane and its preparation method and application, which forms a polyamide separation layer by depositing a two-dimensional nanomaterial interlayer on the surface of a macroporous substrate, thereby preventing monomers from penetrating into the substrate pores, reducing mass transfer resistance and alleviating internal concentration polarization. However, the preparation process of this method is complex, the material cost is high, and the long-term stability and adaptability to complex environments have not been verified, and there are environmental hazards in the use of organic solvents and high-temperature treatment. Patent CN117899678A discloses a method for preparing an ultra-thin covalent organic polymer membrane by interfacial polymerization, which limits the diffusion of aldehyde monomers by using glue base functional groups on the surface of the substrate, forms an ultra-thin and uniform separation layer, and uses the glue base to participate in the reaction to enhance the bonding force between the separation layer and the substrate, thereby improving the permeability and organic dye retention rate of the membrane. However, this method requires complex processes such as glue base modification of the substrate by diazotization induction anchoring, which increases the preparation cost and the complexity of the steps; in addition, the use of specific substrate materials (polysulfone) and organic solvents (n-hexane) may limit its universality and environmental friendliness.

[0006] Therefore, in view of the deficiencies in material design and structure regulation of MMMs, it is necessary to provide a new preparation method to solve the problems of filler dispersion, polymer matrix interface compatibility, substrate mass transfer resistance and weak interface bonding. SUMMARY

[0007] To solve the above technical problems, the present application first provides a preparation method of a gradient flat plate ceramic-based mixed matrix membrane.

[0008] The technical scheme adopted by the present application is:

[0009] A preparation method of a gradient flat plate ceramic-based mixed matrix membrane, the gradient flat plate ceramic-based mixed matrix membrane comprising an alumina gradient flat plate ceramic substrate and a mixed matrix membrane arranged on the substrate, the preparation method comprising the following steps:

[0010] S1. Substrate pretreatment: soak the alumina gradient flat plate ceramic substrate in ethanol, then wash it with deionized water, then immerse it in a glutaraldehyde (GA) solution for a set time, and dry it for standby use;

[0011] S2. Aminated UiO-66: disperse zirconium-based metal organic framework material UiO-66 in anhydrous methanol, stir and activate, centrifuge and dry, then disperse in deionized water, add amine source ingredients, stir and react, then centrifuge and collect the product, wash and dry to obtain aminated UiO-66;

[0012] S3. Preparation of mixed matrix membrane slurry: prepare polyvinyl alcohol (PVA) solution, add the amine-based UiO-66, ultrasonic dispersion and stirring reaction, then stand for defoaming, and obtain the mixed matrix membrane slurry;

[0013] S4. Spin coating the mixed matrix membrane slurry obtained in step S3 on the pretreated substrate in step S1, and after natural drying, immerse it in a glutaraldehyde solution for cross-linking reaction for a set time, and then constant temperature drying to obtain the gradient plate ceramic-based mixed matrix membrane.

[0014] Preferably, the alumina gradient plate ceramic substrate is a ceramic substrate comprising at least two hierarchical structures, the two hierarchical structures having different porosities and average pore sizes, and the porosities and average pore sizes gradually increase along the direction from the side contacting the mixed matrix membrane to the substrate.

[0015] Preferably, the alumina gradient plate ceramic substrate is a three-layer composite structure comprising a top layer, a transition layer and a bottom layer, the top layer being the side contacting the mixed matrix membrane, the average pore sizes of the top layer, the transition layer and the bottom layer gradually increase in turn, and the pore sizes are in the range of 0.4 μm to 10.6 μm.

[0016] In this application, the alumina gradient plate ceramic substrate can use commercially available multi-layer plate ceramic substrate that meets the requirements, or can be prepared according to the method disclosed in the inventor's previous patent CN117567141A.

[0017] Preferably, the preparation method of the zirconium-based metal organic framework material UiO-66 is to dissolve zirconium salt in N,N-dimethylformamide (DMF), add terephthalic acid (H2BDC) and a regulator, seal the reaction kettle for solvothermal reaction, centrifuge to collect the product, and wash and dry to obtain the UiO-66.

[0018] Preferably, the zirconium salt is ZrOCl2·8H2O, the regulator is acetic acid, and the molar ratio of the zirconium salt, N,N-dimethylformamide, terephthalic acid and acetic acid is 1:500:(1-4):1.

[0019] Preferably, the solvothermal reaction temperature is 110-140℃, and the reaction time is 12-24h.

[0020] Preferably, in step S1, the ethanol soaking time is 1h, the glutaraldehyde solution concentration is 1-4wt%, and the immersion time is 15min.

[0021] Preferably, in the step S2, the UiO-66 is stirred in anhydrous ethanol at 50℃ for 12h, the amine source component is any one of ethylenediamine (EDA), tetramethyl ethylenediamine (TMEDA), and disodium ethylenediaminetetraacetate (EDTA-2Na), the molar ratio of the UiO-66 to the amine source component is 1:1, and the magnetic stirring reaction is carried out at 60℃ for 24h.

[0022] Preferably, in the step S3, the concentration of the polyvinyl alcohol solution is 10wt%, the amount of the amine-functionalized UiO-66 accounts for 0.5-5.0% of the mass of the polyvinyl alcohol solution, the ultrasonic dispersion time is 0.5-2.0h, and the stirring reaction time is 3-6h.

[0023] Preferably, in the step S4, the spin coating speed is 40-100rpm, the spin coating thickness is 5-20μm, the concentration of the glutaraldehyde solution is 1-4wt%, the crosslinking reaction time is 15min, and the drying temperature is 40℃. The application further provides a gradient flat plate ceramic-based hybrid matrix membrane material prepared by the above preparation method.

[0024] The application further provides an application of the gradient flat plate ceramic-based hybrid matrix membrane material in new energy vehicle coating wastewater purification, textile printing and dyeing wastewater treatment, and / or pervaporation purification.

[0025] The application takes polyvinyl alcohol (PVA) as a polymer phase and amine-functionalized metal organic framework (MOF) UiO-66 nanoparticles as a filler dispersion phase, promotes the dispersion of the filler and enhances the interface bonding strength of the ceramic-membrane layer, and guarantees the high separation performance and mechanical stability of the separation membrane (MMMs). Specifically:

[0026] 1) By means of the unique MOF structure regulation and interface bonding process, the key problem of the compatibility of the filler dispersion and the polymer matrix interface is solved.

[0027] Defective UiO-66 is synthesized by introducing an adjusting agent acetic acid. Subsequently, ethylenediamine is selected to graft the surface of UiO-66 at 60℃ in an aqueous phase, so as to avoid the damage of the traditional strong acid / high-temperature modification to the structure of MOF. The molecular structure of ethylenediamine is simple (double primary amine groups), and the steric hindrance is small, so that the ethylenediamine can be more effectively grafted to the surface of UiO-66 and expose active -NH2 groups. More importantly, the dense and uniform hydrogen bond network can be formed between the exposed primary amine groups (-NH2) and the abundant hydroxyl groups (-OH) on the molecular chain of PVA. The optimized hydrogen bond network not only significantly improves the dispersion uniformity of UiO-66 in the PVA matrix (effectively inhibits agglomeration), but also greatly enhances the interface compatibility and stress transfer efficiency of the filler and the polymer matrix as a “molecular bridge”.

[0028] 2) In order to solve the problem of insufficient adhesion between the substrate and the membrane layer, glutaraldehyde (GA) is used to pretreat the porous alumina ceramic substrate. The aldehyde group (-CHO) of GA can react with the trace amount of hydroxyl group (-OH) on the surface of the alumina (Al2O3) ceramic or the active sites exposed after cleaning, thereby forming an aldehyde group-rich covalently cross-linked active layer on the substrate surface in situ to improve the interfacial bonding strength. The casting solution containing amine-functionalized UiO-66 (rich in -NH2) and PVA (rich in -OH) is coated on the pretreated substrate, and GA solution is used again for cross-linking. In this process, GA plays a dual cross-linking role: the aldehyde group of GA reacts with the -OH of PVA and the -NH2 of amine-functionalized UiO-66 to form stable covalent bonds (such as imine bonds C=N), thereby solidifying the membrane layer structure and improving its mechanical strength and stability. The GA molecules can simultaneously react with the aldehyde group (or its derivatives) of the active layer on the substrate surface and the -OH of PVA or the -NH2 of amine-functionalized UiO-66 in the separation layer, thereby forming a firm covalent bond "bridge" at the substrate-separation layer interface. This GA-mediated "covalent bond anchoring" mechanism is a core mechanism that has not been fully utilized in the prior art for strengthening the ceramic / polymer membrane interface, and it fundamentally solves the problems of weak interfacial adhesion and easy peeling.

[0029] Therefore, by optimizing the multi-scale structure of the membrane material, the present application solves the problems of poor dispersion of the separation layer filler, weak interfacial adhesion and high mass transfer resistance of the substrate. The material and preparation method provided by the present application have the advantages of selectivity, mechanical stability and green process.

[0030] Experiments have proved that, compared with the existing mixed matrix membrane preparation technology, the present application has the following beneficial effects:

[0031] 1) The gradient flat plate ceramic-based mixed matrix membrane material provided by the present application is a high-performance composite membrane in which amine-functionalized UiO-66 / PVA is supported by a gradient-pore ceramic flat plate. By using a ceramic flat plate with gradient pores as a substrate to reduce the mass transfer resistance, the filtration flux of the composite membrane is effectively improved.

[0032] 2) EDA is used to graft UiO-66 in an aqueous phase, introducing -NH2 groups to form a hydrogen bond network with PVA, so that the filler is uniformly dispersed, and the Cu 2+ adsorption capacity reaches 51.36 mg / g.

[0033] 3) By pretreating the substrate with 3wt% glutaraldehyde, the interfacial adhesion between the separation layer and the substrate is enhanced, and the membrane surface fracture toughness is improved to 18.3 MPa. After Cu 2+ cycles, the rejection rate is >67%, and no interface peeling or cracking occurs between the separation layer and the ceramic substrate.

[0034] 4) The use of aqueous amine functionalization and low-temperature crosslinking results in low energy consumption and no organic waste emissions. The substrate adaptability is strong, and the filler modification strategy can be extended to other MOFs, which has potential for industrial application and is suitable for practical use. BRIEF DESCRIPTION OF DRAWINGS

[0035] Figure 1 Water flux analysis results of the gradient flat plate ceramic-based hybrid matrix membranes prepared for Examples 1-9 and Comparative Examples 1-3.

[0036] Figure 2 Copper ion rejection change analysis results of the gradient flat plate ceramic-based hybrid matrix membranes prepared for Examples 1-9 and Comparative Examples 1-3.

[0037] Figure 3 Ferrous ion rejection change analysis results of the gradient flat plate ceramic-based hybrid matrix membranes prepared for Examples 1-9 and Comparative Examples 1-3.

[0038] Figure 4 Manganese ion rejection change analysis results of the gradient flat plate ceramic-based hybrid matrix membranes prepared for Examples 1-9 and Comparative Examples 1-3.

[0039] Figure 5 Fluoride ion rejection change analysis results of the gradient flat plate ceramic-based hybrid matrix membranes prepared for Examples 1-9 and Comparative Examples 1-3.

[0040] Figure 6 Hardness test results of the gradient flat plate ceramic-based hybrid matrix membranes prepared for Examples 1-9 and Comparative Examples 1-3.

[0041] Figure 7 Fracture toughness results of the gradient flat plate ceramic-based hybrid matrix membranes prepared for Examples 1-9 and Comparative Examples 1-3.

[0042] Figure 8 Fourier infrared spectrograms of different components of the gradient flat plate ceramic-based hybrid matrix membrane prepared for Example 9.

[0043] Figure 9 Pervaporation diagram of the gradient flat plate ceramic-based hybrid matrix membrane prepared for Example 9.

[0044] Figure 10 Scanning electron microscope diagram of the surface of the gradient flat plate ceramic-based hybrid matrix membrane prepared for Example 9.

[0045] Figure 11 Scanning electron microscope diagram of the cross section of the gradient flat plate ceramic-based hybrid matrix membrane prepared for Example 9. DETAILED DESCRIPTION

[0046] In order to facilitate understanding, the technical solutions of the present application will be described in more detail below in conjunction with examples.

[0047] Unless otherwise specified, all the raw materials, reagents, instruments and equipment used in the present application can be purchased from the market or prepared by the existing methods.

[0048] Example 1

[0049] A method for preparing a gradient plate ceramic-based mixed matrix membrane, comprising the following steps:

[0050] S1. Preparation of UiO-66: 2.01 g of ZrOCl2·8H2O was dissolved in 240.00 mL of DMF under magnetic stirring, then 1.04 g of H2BDC and 30.00 mL of acetic acid modifier were added to the solution, stirred until completely dissolved, and the mixed solution was sealed in an autoclave and reacted at 110℃ for 12 h, followed by centrifugal collection of the product UiO-66, which was washed with ethanol several times and dried.

[0051] S2. Amination of UiO-66: UiO-66 was dispersed in anhydrous methanol at 50℃, activated by stirring for 12 h, dried by centrifugation, and then ultrasonically dispersed in deionized water, EDA was added at a molar ratio of 1:1 with UiO-66, and the mixture was stirred magnetically at 60℃ for 24 h, the product was collected by centrifugation, washed and dried to obtain aminated UiO-66;

[0052] S3. Preparation of mixed matrix membrane slurry: PVA was dissolved in deionized water to prepare a 10wt% solution, 0.5wt% of aminated UiO-66 was added to the PVA solution, ultrasonically dispersed and stirred for a certain time, and then left to stand to remove bubbles, to obtain a UiO-66-EDA mixed matrix membrane slurry;

[0053] S4. Substrate pretreatment: The alumina gradient plate ceramic substrate was soaked in ethanol for 1 h, washed with deionized water, and then immersed in a 3wt% GA solution for 15 min and dried for use;

[0054] In this example, the alumina gradient plate ceramic substrate has a top layer, a transition layer and a bottom layer from the side in contact with the mixed matrix membrane to the bottom side, and the average pore size of the top layer, the transition layer and the bottom layer is 0.42 μm, 2.6 μm and 10.5 μm, respectively.

[0055] S5. The mixed matrix membrane slurry was spin-coated on the pretreated substrate at a spin-coating speed of 80 rpm, and the film thickness was 16.32 μm. After natural drying, the substrate was immersed in a 3wt% GA solution for crosslinking for 15 min, and then dried at 40℃ to obtain a gradient plate ceramic-based mixed matrix membrane.

[0056] Example 2

[0057] A method for preparing a gradient plate ceramic-based mixed matrix membrane, comprising the following steps:

[0058] S1. Preparation of UiO-66: 2.01 g of ZrOCl2·8H2O was dissolved in 240.00 mL of DMF under magnetic stirring, then 1.04 g of H2BDC and 30.00 mL of acetic acid modifier were added to the solution, stirred until completely dissolved, and the mixed solution was sealed in an autoclave and reacted at 110°C for 12 h, followed by centrifugal collection of the product UiO-66, which was washed with ethanol several times and dried.

[0059] S2. Amination of UiO-66: UiO-66 was dispersed in anhydrous methanol at 50°C, activated by stirring for 12 h, dried by centrifugation, and then ultrasonically dispersed in deionized water, 1:1 molar ratio of EDA was added to UiO-66, and the mixture was stirred magnetically at 60°C for 24 h, the product was collected by centrifugation, washed and dried to obtain aminated UiO-66;

[0060] S3. Preparation of mixed matrix membrane slurry: PVA was dissolved in deionized water to prepare a 10wt% solution, 1% of aminated UiO-66 based on the mass of PVA solution was added, ultrasonically dispersed and stirred for a certain time, and after standing to remove bubbles, a UiO-66-EDA mixed matrix membrane slurry was obtained;

[0061] S4. Substrate pretreatment: the alumina gradient plate ceramic substrate was soaked in ethanol for 1 h, washed with deionized water, then immersed in a 3wt% GA solution for 15 min, and dried for use;

[0062] S5. The mixed matrix membrane slurry was spin-coated on the pretreated substrate at a spin-coating speed of 80 rpm, a film thickness of 16.28 μm was formed, and after natural drying, the substrate was immersed in a 3wt% GA solution for crosslinking for 15 min, and then dried at 40°C to obtain a gradient plate ceramic-based mixed matrix membrane.

[0063] Example 3

[0064] A method for preparing a gradient plate ceramic-based mixed matrix membrane, comprising the following steps:

[0065] S1. Preparation of UiO-66: 2.01 g of ZrOCl2·8H2O was dissolved in 240.00 mL of DMF under magnetic stirring, then 1.04 g of H2BDC and 30.00 mL of acetic acid modifier were added to the solution, stirred until completely dissolved, and the mixed solution was sealed in an autoclave and reacted at 110°C for 12 h, followed by centrifugal collection of the product UiO-66, which was washed with ethanol several times and dried.

[0066] S2. Aminated UiO-66: UiO-66 was dispersed in anhydrous methanol at 50°C, activated by stirring for 12 h, dried by centrifugation, and then dispersed in deionized water by ultrasonic dispersion. EDA was added at a molar ratio of 1:1 with UiO-66, and the reaction was carried out by magnetic stirring at 60°C for 24 h. The product was collected by centrifugation, washed and dried to obtain aminated UiO-66;

[0067] S3. Preparation of mixed matrix membrane slurry: PVA was dissolved in deionized water to prepare a 10wt% solution, and aminated UiO-66 was added at 2.5% of the mass of the PVA solution. The mixture was ultrasonically dispersed and stirred for a set time, and then left to stand to remove bubbles. A UiO-66-EDA mixed matrix membrane slurry was obtained.

[0068] S4. Substrate pretreatment: The alumina gradient plate ceramic substrate was soaked in ethanol for 1 h, washed with deionized water, and then immersed in a 3wt% GA solution for 15 min. The substrate was dried and ready for use.

[0069] S5. The mixed matrix membrane slurry was spin-coated on the pretreated substrate at a spin-coating speed of 80 rpm, and a film thickness of 16.38 μm was obtained. After natural drying, the substrate was immersed in a 3wt% GA solution for crosslinking for 15 min, and then dried at a constant temperature of 40°C to obtain a gradient plate ceramic mixed matrix membrane.

[0070] Example 4

[0071] The preparation method of this example is the same as that of Example 1, except that TMEDA is used as the amine source component.

[0072] Example 5

[0073] The preparation method of this example is the same as that of Example 2, except that TMEDA is used as the amine source component.

[0074] Example 6

[0075] The preparation method of this example is the same as that of Example 3, except that TMEDA is used as the amine source component.

[0076] Example 7

[0077] The preparation method of this example is the same as that of Example 1, except that EDTA-2Na is used as the amine source component.

[0078] Example 8

[0079] The preparation method of this example is the same as that of Example 2, except that EDTA-2Na is used as the amine source component.

[0080] Example 9

[0081] The preparation method of this embodiment is the same as that of Example 3, except that the amine source component uses EDTA-2Na.

[0082] Comparative Example 1

[0083] A preparation method of a gradient plate ceramic-based mixed matrix membrane, comprising the following steps:

[0084] S1. Preparation of UiO-66: 2.01 g of ZrOCl2·8H2O was dissolved in 240.00 mL of DMF under magnetic stirring, then 1.04 g of H2BDC and 30.00 mL of acetic acid modifier were added to the solution, stirred until completely dissolved, the mixed solution was sealed in an autoclave, reacted at 110°C for 12 h, then the product UiO-66 was collected by centrifugation, washed with ethanol for several times and dried.

[0085] S2. Preparation of mixed matrix membrane slurry: PVA was dissolved in deionized water to prepare a 10wt% solution, 0.5% of UiO-66 based on the mass of the PVA solution was added, ultrasonic dispersion and stirring for a set time, after standing and defoaming, the UiO-66-EDA mixed matrix membrane slurry was obtained;

[0086] S3. Substrate pretreatment: the alumina gradient plate ceramic substrate was soaked in ethanol for 1 h, then washed with deionized water, then immersed in a 3wt% GA solution for 15 min, and dried for standby;

[0087] S4. The mixed matrix membrane slurry was spin-coated on the pretreated substrate at a spin-coating speed of 80 rpm, and the film thickness was 17.25 μm. After natural drying, it was immersed in a 3wt% GA solution for crosslinking for 15 min, and then dried at 40°C to obtain a gradient plate ceramic-based mixed matrix membrane.

[0088] Comparative Example 2

[0089] A preparation method of a gradient plate ceramic-based mixed matrix membrane, comprising the following steps:

[0090] S1. Preparation of UiO-66: 2.01 g of ZrOCl2·8H2O was dissolved in 240.00 mL of DMF under magnetic stirring, then 1.04 g of H2BDC and 30.00 mL of acetic acid modifier were added to the solution, stirred until completely dissolved, the mixed solution was sealed in an autoclave, reacted at 110°C for 12 h, then the product UiO-66 was collected by centrifugation, washed with ethanol for several times and dried.

[0091] S2. Preparation of mixed matrix membrane slurry: PVA was dissolved in deionized water to prepare a 10wt% solution, 0.5% of UiO-66 based on the mass of the PVA solution was added, ultrasonic dispersion and stirring for a set time, after standing and defoaming, the UiO-66-EDA mixed matrix membrane slurry was obtained;

[0092] S3. Substrate pretreatment: immerse the alumina gradient plate ceramic substrate in ethanol for 1 h, then clean with deionized water, then immerse in a 1 wt% GA solution for 15 min, and dry for standby;

[0093] S4. Spin the mixed matrix membrane slurry on the pretreated substrate at a spin speed of 80 rpm, with a film thickness of 17.38 μm, naturally dry, then immerse in a 3 wt% GA solution for crosslinking for 15 min, and dry at a constant temperature of 40°C to obtain a gradient plate ceramic-based mixed matrix membrane.

[0094] Comparative Example 2

[0095] A method for preparing a gradient plate ceramic-based mixed matrix membrane, comprising the following steps:

[0096] S1. Preparation of UiO-66: under magnetic stirring, dissolve 2.01 g of ZrOCl2·8H2O in 240.00 mL of DMF, then add 1.04 g of H2BDC and 30.00 mL of acetic acid modifier to the solution, stir until completely dissolved, seal the mixed solution in an autoclave, and react at 110°C for 12 h, then centrifuge to collect the product UiO-66, wash with ethanol several times, and dry.

[0097] S2. Preparation of mixed matrix membrane slurry: dissolve PVA in deionized water to prepare a 10 wt% solution, add 0.5% of UiO-66 based on the mass of the PVA solution, ultrasonic dispersion and stirring for a set time, and after standing to remove bubbles, obtain a UiO-66-EDA mixed matrix membrane slurry;

[0098] S3. Substrate pretreatment: immerse the alumina gradient plate ceramic substrate in ethanol for 1 h, then clean with deionized water, then immerse in a 2.5 wt% GA solution for 15 min, and dry for standby;

[0099] S4. Spin the mixed matrix membrane slurry on the pretreated substrate at a spin speed of 90 rpm, with a film thickness of 17.15 μm, naturally dry, then immerse in a 3 wt% GA solution for crosslinking for 15 min, and dry at a constant temperature of 40°C to obtain a gradient plate ceramic-based mixed matrix membrane.

[0100] Results analysis:

[0101] The gradient flat plate ceramic-based hybrid matrix membranes prepared in Examples 1-3 are denoted as UiO-66-EDA-PVA, the gradient flat plate ceramic-based hybrid matrix membranes prepared in Examples 4-6 are denoted as UiO-66-TMEDA-PVA, the gradient flat plate ceramic-based hybrid matrix membranes prepared in Examples 7-9 are denoted as UiO-66-EDTA-PVA, and the gradient flat plate ceramic-based hybrid matrix membranes prepared in Comparative Examples 1-3 are denoted as UiO-66-PVA.

[0102] The water flux analysis results of the gradient flat plate ceramic-based hybrid matrix membranes prepared in Examples 1-9 and Comparative Examples 1-3 are shown in Table Figure 1 , the copper ion interception change analysis results are shown in Table Figure 2 , the ferrous ion interception change analysis results are shown in Table Figure 3 , the manganese ion interception change analysis results are shown in Table Figure 4 , the fluoride ion interception change analysis results are shown in Table Figure 5 , the hardness and fracture toughness analysis results of the composite membranes are shown in Table Figure 6 and Figure 7 . The results shown in the tables are obtained by determining the concentration changes of the target ions (Cu 2+ , Fe 2+ , Mn 2+ , F-) before and after the treatment solution passes through the gradient flat plate ceramic-based hybrid matrix membranes. The concentration determination method refers to the standard methods such as HJ 345-2007, GB / T 11906-1989 and GB / T 7483-1987, and the linear relationship between the absorbance of the complex generated by the reaction of the ion with the specific color developing agent at the characteristic wavelength and the concentration is used to realize accurate quantification. The microhardness determination refers to the test method in the literature "Research on Microstructure and Properties of WC-Ti(C, N)-NbC-HEA Cemented Carbide Materials", and the crack length is measured during the Vickers hardness test process, and the fracture toughness is calculated according to the formula . In the formula, K IC is the fracture toughness (unit: MPa·m 1 / 2 ); H is the Vickers hardness (unit: HV); E is the elastic modulus (390 GPa for the ceramic substrate Al2O3 and 40 GPa for PVA); φ is the shape factor (3); a is the indentation half-length; and l is the crack length.

[0103] Figures 1-5 The performance test of the composite membranes shows that the UiO-66-EDA-PVA membrane modified by EDA exhibits excellent water flux and ion interception synergistic performance. At a loading of 1 wt%, the water flux reaches 664.63 L·m -2• h-1, significantly higher than the unmodified UiO-66-PVA membrane (Comparative Example 1, 252.10 L-m -2 • h-1). At the same time, the rejection of various ions by the membrane was significantly improved, with a fluoride ion rejection rate of 29.28%, a ferrous ion rejection rate of 40.79%, a manganese ion rejection rate of up to 37.48%, and a copper ion rejection rate of 76.19%. At a loading of 2.5 wt%, the UiO-66-EDA-PVA membrane maintained a copper ion rejection rate of 67.37%, while the rejection rate of the TMEDA modified membrane at the same loading dropped to 5.64%, highlighting the stability advantage of the EDA modified membrane.

[0104] Figures 6-7 It is shown that with the increase of UiO-66 loading, the hardness and fracture toughness of all composite membranes show a synergistic improvement trend, which is related to the nanofiller reinforcement effect. It is particularly noteworthy that although the TMEDA and EDTA-2Na functionalized membranes exhibit excellent mechanical properties, their separation effect is poor, which indirectly indicates that their filler dispersion is poor and there are interface defects. In contrast, although the mechanical properties of the EDA functionalized membrane increase relatively small, it exhibits excellent ion rejection performance, and it can be known that the performance is optimal when the loading is 1.00 wt%, the surface hardness of the membrane reaches 183.4 HV, and the fracture toughness is 25.43 MPa-m -1 / 2 . And from Figure 9 it can be seen that the water selective permeation potential exhibited by the EDA modified membrane is particularly suitable for alcohol dehydration and organic solvent purification. In the future, by optimizing the MOF functionalization strategy (such as -SO3H modification) and regulating the cross-linked network, its separation performance in high concentration organic system can be further improved, and its industrial applications in biofuel dehydration, petrochemical wastewater treatment, etc. are promoted.

[0105] It can be seen that the amine modification of UiO-66 by ethylenediamine (EDA) has the best comprehensive performance, and the cross-linking of EDA to the PVA network by glutaraldehyde forms a composite membrane material. Figure 8 Infrared spectroscopy provides key evidence for the modification and cross-linking process: new characteristic peaks at 3100 cm -1 and 3060 cm -1 confirm that ethylenediamine is grafted to the benzene ring of UiO-66 to form a monosubstituted structure, significantly changing the C-H vibration mode of the aromatic ring; the increase in the absorption peak at 1680 cm -1 is mainly due to the imine bond (C=N) generated by the reaction of glutaraldehyde with the primary amine group of UIO-66-NH2, which directly verifies the occurrence of the cross-linking reaction; the new sharp peak at 1580 cm -1 is clearly attributed to the N-H bending vibration of the grafted primary amine group (-NH2), further supporting the success of the amine modification.

[0106] Moreover, the application solves the key problem of filler dispersion and polymer matrix interface compatibility through the unique MOF structure regulation and interface combination process. Unlike traditional strong acid etching or high temperature modification methods (such as CN115228311A requiring concentrated nitric acid treatment), acetic acid is innovatively used as a crystal lattice defect inducer to precisely regulate the UiO-66 pore structure (Zr salt: ligand: acetic acid = 1:1-4:1) under mild solvothermal conditions (110-140℃). This controllable defect design significantly increases the surface active site, laying a foundation for subsequent functionalization. More innovatively, a water phase amine functionalization-crosslinking synergistic process is developed: in a water phase environment at 60℃, EDA is grafted with MOF in a 1:1 molar ratio in an "end bridging" mode, forming a -NH2 functional layer Figure 8 , and the 3100cm -1 C-H vibration peak shift in infrared spectrum proves), and more importantly, the double primary amine groups (-NH2) of EDA and the hydroxyl groups (-OH) of PVA form a dense "MOF-NH2…HO-PVA" hydrogen bond network Figure 8 , and the 1580cm -1 characteristic peak shift in infrared spectrum confirms): the bidirectional hydrogen bonding ability (donor + acceptor) of the primary amine group forms "MOF-NH2···HO-PVA" and "PVA-O···H2N-MOF" bidirectional bonding, which effectively disperses stress when the membrane is under pressure, avoiding interface cracking; at the same time, GA is used as a molecular bridge, and its aldehyde group reacts with the amine group of MOF and the hydroxyl group of PVA to form an imine bond Figure 8 , 1680cm -1 C=N peak), constructing a three-dimensional interpenetrating network. This dual interface strengthening mechanism enables uniform dispersion of nanoparticles at a filler loading of 1wt% Figure 10 、 Figure 11 SEM images verify), which greatly improves performance - water flux reaches 664.63L·m -2 ·h -1 (163% higher than the unmodified membrane), Cu 2+ retention rate breaks through to 76.2%, and adsorption capacity reaches 51.36mg / g.

[0107] Secondly, to solve the problem of weak interfacial adhesion and mass transfer resistance, the application utilizes alumina gradient plate ceramic substrate with "micro-mesoporous-macroporous" ladder structure characteristics to create a low shear environment for MOF / PVA layer. The alumina gradient plate ceramic substrate in this application can adopt the multi-layer co-fired alumina ceramic plate support with gradient pore structure proposed in the inventor's previous patent CN117567141A, realize the gradient substrate-casting solution interlocking structure model, and break through the mass transfer resistance limitation of traditional single pore size distribution ceramic substrate. More importantly, by pretreating the substrate with 3wt% glutaraldehyde for 15 minutes, an aldehyde active layer (-CHO) is constructed on the ceramic surface, and the substrate-MOF direct bonding is achieved through Schiff base reaction, which enhances the stability of the filler interface. The semi-acetal reaction covalently grafts PVA chains to the substrate surface, and the ether bond bridge expands to a three-dimensional network, improving the toughness of the membrane layer and realizing the "ceramic-GA-PVA" three-level molecular anchoring (cross-sectional SEM Figure 11 showing no delamination). This structural innovation combined with the nano-enhancing effect of MOF filler forms a unique mechanical stability system: gradient pore size disperses operating stress, MOF acts as "nanosize rivets", and GA crosslinking network provides energy dissipation paths, which synergistically improves the fracture toughness to 25.43 MPa·m -1 / 2 ( Figure 7 ), which is 1.7 times that of commercial ceramic membranes. After 5 cycles of Cu 2+ circulation test, the retention rate is stable >67%, and the flux attenuation is <5% under high pressure of 0.8 MPa for 120 hours, completely solving the high pressure peeling problem of traditional membranes.

[0108] The application forms a deep synergistic integration of gradient ceramic substrate and hybrid matrix membrane material. The gradient substrate reduces mass transfer resistance and creates an efficient mass transfer environment for the MOF / PVA separation layer; the MOF amination enhances ion selectivity, and the GA crosslinking simultaneously strengthens the filler-polymer interface and the membrane layer-substrate interface, forming a multi-level stable structure. Compared with existing technologies, this scheme has significant advantages: compared with the graphene intermediate layer process of CN112023732A, the high temperature deposition step of 300℃ is omitted; compared with the diazo anchoring method of CN117899678A, the ceramic surface hydroxyl group is directly utilized for green modification; compared with the amidoxime group modification of CN115228311A, the aqueous phase process avoids organic solvent emission (cost reduction of 40%). These innovations make the gradient plate ceramic hybrid matrix membrane provided by the application expected to realize "one membrane for multiple purposes" in new energy vehicle wastewater (high Cu 2+ load), fluorine contaminated groundwater (F- retention rate of 29.3%), and pervaporation (ethanol dehydration flux >200g·m -2 ·h-1) scenarios. The aqueous phase reaction, low temperature crosslinking (40℃) green characteristics, combined with the MOF modification strategy, are applicable to ZIF-8 and other systems, providing a new paradigm for industrial grade high performance separation membrane development.

[0109] The above embodiments are only used to illustrate the technical solutions of the present application, and are not intended to limit the present application; even though the present application has been described in detail with reference to the foregoing embodiments, those ordinarily skilled in the art should understand that any modification, equivalent replacement and improvement made within the spirit and principle of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a gradient flat-plate ceramic-based hybrid matrix membrane, characterized in that, The gradient flat ceramic-based hybrid matrix membrane comprises an alumina gradient flat ceramic substrate and a hybrid matrix membrane disposed on the substrate, and the preparation method includes the following steps: S1. Substrate pretreatment: The alumina gradient flat ceramic substrate is soaked in ethanol, rinsed with deionized water, then immersed in glutaraldehyde solution for a set time, and dried for later use. S2. Amination of UiO-66: Zirconium-based metal-organic framework material UiO-66 was dispersed in anhydrous methanol, stirred and activated, centrifuged and dried, ultrasonically dispersed in deionized water, added amine source components, stirred and reacted, centrifuged and collected the product, washed and dried to obtain amination of UiO-66. S3. Preparation of mixed matrix membrane slurry: Prepare a polyvinyl alcohol solution, add the amination-modified UiO-66, ultrasonically disperse and stir to react, and then let stand to defoam to obtain mixed matrix membrane slurry; S4. Spin-coat the mixed matrix membrane slurry obtained in step S3 onto the substrate pretreated in step S1, let it dry naturally, then immerse it in glutaraldehyde solution for a set time for crosslinking reaction, and finally dry it at a constant temperature to obtain the gradient flat ceramic matrix mixed matrix membrane.

2. The method for preparing a gradient flat-plate ceramic-based hybrid matrix membrane as described in claim 1, characterized in that, The alumina gradient flat ceramic substrate is a ceramic substrate comprising at least two hierarchical structures, the two hierarchical structures having different porosities and average pore sizes, and the porosity and average pore size gradually increasing along the direction from the side of the contact mixing matrix film to the substrate.

3. The method for preparing a gradient flat-plate ceramic-based hybrid matrix membrane as described in claim 1, characterized in that, The zirconium-based metal-organic framework material UiO-66 is prepared by dissolving zirconium salt in N,N-dimethylformamide, adding terephthalic acid and a regulator, sealing the reaction vessel for a solvothermal reaction, collecting the product by centrifugation, washing and drying to obtain UiO-66.

4. The method for preparing a gradient flat-plate ceramic-based hybrid matrix membrane as described in claim 3, characterized in that, The zirconium salt is ZrOCl2·8H2O, the regulator is acetic acid, and the molar ratio of zirconium salt, N,N-dimethylformamide, terephthalic acid and acetic acid is 1:500:(1~4):1; the solvothermal reaction temperature is 110~140℃, and the reaction time is 12~24h.

5. The method for preparing a gradient flat-plate ceramic-based hybrid matrix membrane as described in claim 1, characterized in that, In step S1, the ethanol soaking time is 1 hour, the glutaraldehyde solution concentration is 1-4 wt%, and the soaking time is 15 minutes.

6. The method for preparing a gradient flat-plate ceramic-based hybrid matrix membrane as described in claim 1, characterized in that, In step S2, UiO-66 is activated by stirring in anhydrous ethanol at 50°C for 12 hours. The amine source component is any one of ethylenediamine, tetramethylethylenediamine, or disodium ethylenediaminetetraacetate. The molar ratio of UiO-66 to the amine source component is 1:

1. The reaction is carried out by magnetic stirring at 60°C for 24 hours.

7. The method for preparing a gradient flat-plate ceramic-based hybrid matrix membrane as described in claim 1, characterized in that, In step S3, the concentration of the polyvinyl alcohol solution is 10 wt%, the amount of amination-modified UiO-66 is 0.5-5.0% of the mass of the polyvinyl alcohol solution, the ultrasonic dispersion time is 0.5-2.0 h, and the stirring reaction time is 3-6 h.

8. The method for preparing a gradient flat-plate ceramic-based hybrid matrix membrane as described in claim 1, characterized in that, In step S4, the spin coating speed is 40-100 rpm, the spin coating thickness is 5-20 μm, the glutaraldehyde solution concentration is 1-4 wt%, the crosslinking reaction time is 15 min, and the drying temperature is 40 °C.

9. A gradient flat ceramic matrix hybrid matrix membrane material prepared by the preparation method according to any one of claims 1-8.

10. The application of the gradient flat ceramic matrix hybrid matrix membrane material as described in claim 9 in the purification of new energy vehicle coating wastewater and / or the treatment and / or pervaporation purification of textile dyeing wastewater.

Citation Information

Patent Citations

  • Forward osmosis composite membrane and preparation method and application thereof

    CN112023732A

  • Preparation method of PIM-1 mixed matrix membrane based on amidoxime group modified UiO-66 material

    CN115228311A

  • Method for preparing ultrathin covalent organic polymer film through interfacial polymerization

    CN117899678A